Adherence to urate-lowering therapy while following the national guidelines for the management of patients with gout (preliminary evidence) - M. N. Chikina; E. V. Ilyinykh; M. S. Eliseev (Современная ревматология)
Low compliance in patients with gout is one of the reasons for inadequate disease control.Objective: to study treatment adherence in compliance with the national guidelines for the management of gout patients, which provide for the continuous use of urate-lowering drugs, a gradual increase in their dose until the target serum uric acid (UA) level is reached, prophylactic antiinflammatory therapy, and regular patient monitoring.Patients and methods. This was a prospective single-center study. By now, 60 of the 80 enrolled gout patients had completed the study. The follow-up period was at least 24 weeks, during which allopurinol or febuxostat was used at the final dose. During initiation of urate-lowering therapy, allopurinol 100 mg/day was prescribed, followed by dose titration to reach the target UA level (<360 μmol/L) for all patients or <300 μmol/L for those with severe tophaceous gout. Patients with ineffective allopurinol and/or in the presence of its associated adverse reactions were prescribed febuxostat (Azurix®) 80 mg/day; the dose was increased up to 120 mg/day as needed. To prevent acute arthritis attacks, all the patients received a nonsteroidal anti-inflammatory drug (NSAID) at minimal therapeutic doses or colchicine 0.5 mg/day, and in the presence of contraindications to their use, they took glucocorticoid (GC) 7.5 mg/day calculated with reference to prednisolone. The four-item Morisky–Green questionnaire was used to assess patient adherence to therapy.Results and discussion. At 24 weeks after the start of their follow-up, 53 (88%) of the 60 patients received urate-lowering therapy; 38 (72%) of these 53 patients achieved the target UA level. The dose of allopurinol was titrated in 19 patients; and 10 (53%) of them achieved the target serum UA levels. Due to its inefficacy, allopurinol was replaced by febuxostat in 24 patients. In this group, the target UA level was recorded in 16 (67%) patients. Seventeen patients were immediately prescribed febuxostat that could achieve the target UA level in 12 (71%) of them. All the patients enrolled in the study received prophylactic anti-inflammatory therapy: NSAIDs were used in 9 (15%) patients, colchicine and GC were given to 46 (77%) and 5 (8%), respectively. Twenty-six (49%) patients who had completed the investigation were ascertained to have a high adherence therapy. Moderate and low adherence was observed in 9 (17%) and 18 (34%) patients, respectively. High therapy adherence was noted in more than half of cases in the febuxostat group and in 40% in the allopurinol one.Conclusion. High compliance in gout patients can be achieved through the observance of the national guidelines for the treatment of this disease.